2011
DOI: 10.1007/s10592-011-0302-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic signature of a severe forest fire on the endangered Gran Canaria blue chaffinch (Fringilla teydea polatzeki)

Abstract: Habitat destruction has been identified as one of the main threats to biodiversity. Among all factors causing habitat disturbance, wildfire is recognized as one of the most important ecological forces that influences not only the physical environment, but also the structure and composition of floral and faunal communities. These processes are often translated in population bottlenecks, which occur frequently in threatened species and result in loss of genetic diversity and evolutionary potential. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Of those focusing on sampling before and after a specific fire, one study on chaffinches ( Fringilla teydea polatzeki) found no impact on population inbreeding or genetic richness (Suárez et al . ), and another on lizards ( Amphibolurus norrisi and Ctenotus atlas ) a decrease in genetic diversity but no concurrent effects on gene flow or population genetic structure (Smith et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those focusing on sampling before and after a specific fire, one study on chaffinches ( Fringilla teydea polatzeki) found no impact on population inbreeding or genetic richness (Suárez et al . ), and another on lizards ( Amphibolurus norrisi and Ctenotus atlas ) a decrease in genetic diversity but no concurrent effects on gene flow or population genetic structure (Smith et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of the few studies on other faunal groups have been mixed, with one finding evidence of changes in allele frequencies but not of population bottlenecks post‐fire (Suárez et al . ) and another finding both increasing and decreasing genetic diversity (Smith et al . ).…”
Section: Introductionmentioning
confidence: 95%
“…Despite a 50% decline in the global population of this sub-species (from about 250 to 122 individuals), temporal sampling found no genetic signature of a bottleneck. Furthermore, the post-fire population retained a high level of genetic diversity [69]. Studies directly examining the effect of fire on genetic signatures of species or populations are rare and, because of the complex nature of fire regimes, offer little in the way of direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Unburnt refuges were prevalent throughout the fire area and were thought to enable a sufficient proportion of individuals to survive and persist, thereby mitigating the loss of genetic variability in the post-bottleneck population [69]. In-situ survivorship in unburnt refuges has been attributed to the rapid demographic recovery in birds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances of spatial population structure may also influence the viability of populations. Previous studies have evaluated the genetic impacts of the Chi-Chi Earthquake in Taiwan on an endangered plant species (Hung et al 2005), floods on an abundant gastropod species (Evanno et al 2009) and mice (Vignieri 2010), forest fires on a tailed frog (Spear and Storfer 2010) and a bird species (Suárez et al 2012), volcanic eruptions on a tailed frog (Spear et al 2012), and hurricanes on a coastal fish species, sailfin molly (Apodaca et al 2013). All of these studies reported a decrease or increase in genetic diversity after a natural disturbance, but only one study, of the sailfin molly, detected a change Abstract We evaluated the effect of the Great Tohoku earthquake, which occurred on March 11, 2011 in Japan, on the genetic diversity and population structure of Pacific herring (Clupea pallasii).…”
Section: Introductionmentioning
confidence: 99%